Management of the communal local public administration in Romania - Vlavian –Gurmeza, Maria; Stefanica, Mirela (Studies and Scientific Researches. Economics Edition, 2010)
The public administration may be defined as the fundamental form of activity of the state, applied by the bodies of the public administration, which consists in exercising the law by establishing some obligatory conducts, as well as by providing services.